2019
DOI: 10.1021/acsnano.8b06189
|View full text |Cite
|
Sign up to set email alerts
|

End-Sealed High Aspect Ratio Hollow Nanotubes Encapsulating an Anticancer Drug: Torpedo-Shaped Peptidic Nanocapsules

Abstract: Nanomaterial morphology is important for the targeted delivery of drugs to tissues as well as subsequent cellular uptake. Hollow nanotubes composed of peptides, with a diameter of 80 nm and various lengths (100, 200, 300, 600 nm), were successfully capped and sealed with a peptide hemisphere to encapsulate the anticancer drug, cisplatin. The torpedo-shaped nanocapsules with an aspect ratio (length/diameter) of 2.4 showed more rapid cellular uptake and accumulation at the tumor site compared with spherical anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 34 publications
6
46
0
Order By: Relevance
“…A ‘patched’ hollow peptide tube can be engineered by mixing two types of peptides, which individually self-assemble into tubular and spherical structures, respectively. The hollow tube is sealed on both ends by half-spheres 146 , and can be applied as a drug-encapsulating vehicle, enabling extravasation into tumour tissue, comparable to other rod-like nanocarriers.…”
Section: Multifunctional Nanostructuresmentioning
confidence: 99%
See 1 more Smart Citation
“…A ‘patched’ hollow peptide tube can be engineered by mixing two types of peptides, which individually self-assemble into tubular and spherical structures, respectively. The hollow tube is sealed on both ends by half-spheres 146 , and can be applied as a drug-encapsulating vehicle, enabling extravasation into tumour tissue, comparable to other rod-like nanocarriers.…”
Section: Multifunctional Nanostructuresmentioning
confidence: 99%
“…To explore the multifunctional advantage of nanomaterials, systems with highly sophisticated spatial structures and responsive mechanisms have been designed 100 , 101 , 146 . However, accurate and reproducible fabrication methods for such complex structures remain limited.…”
Section: Perspectivesmentioning
confidence: 99%
“…The use of peptide-based torpedo-shaped hollow capsules for the delivery of the model anticancer drug: cisplatin. (Adapted with permission from Ueda et al [148] Copyright © 2019, American Chemical Society.) (Online version in colour.)…”
Section: Recent Advances In Complex Hollow Nanostructured Materials Fmentioning
confidence: 99%
“…Recently, peptide-based hollow capsules of variable lengths have been reported as containers for the encapsulation of the model anticancer drug, cisplatin (figure 15). It was observed that the unique shape and high aspect ratio of the capsules provided a fast-cellular uptake and higher accumulation at the tumour site when compared with spherical particles [148].…”
Section: Recent Advances In Complex Hollow Nanostructured Materials Fmentioning
confidence: 99%
“…We previously reported that nanotubes with a uniform diameter of ca. 80 nm were prepared from an amphiphilic block copolypeptide, PSar n - b -( l -Leu-Aib) 6 (SL12) with a hydrophobic α-helix composed of the LxLxLxLxLxLx sequence, which involves two LxxxLxxxL sequences [ 20 , 21 ]. The phenomenon was explained by the hypothesis that the helical part is uniformly packed in a hydrophobic layer due to the concave–convex interaction between helices with the LxxxLxxxL sequence [ 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%